Phenolic Compounds Isolated from Fruits of Cornus officinalis Sieb. et Zucc. - The Hung, Nguyen; Thi Thu, Nguyen; Thi Binh, Bui; Thi Ha, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3DO - 10.25073/2588-1132/vnumps.4216, 2020)
In this study, six phenolic compounds were isolated from the ethyl acetate of Cornus officinalis , including: Gallic acid (1), dimethyl malate (2), 1,4-dimethyl ester 2-(2-formyl-1 H -pyrrol-1-yl)butanedioic acid (3), stageobester A (4), coroffester (5), and methyl caffeate (6). The structure of the compounds was determined by such spectroscopic methods as MS, NMR and by comparison with the published NMR data. This is the first time compounds 3-5 have been isolated from this species. Keywords Cornus officinalis, gallic acid, dimethyl malate, 1,4-dimethyl ester 2-(2-formyl-1H-pyrrol-1-yl)butanedioic acid, stageobester A, coroffester, methyl caffeate. References